ANALISIS PENGEMBANGAN PABRIK PADA INDUSTRI GULA TEBU DI JAWA TIMUR - , Afandi Sudjatmoko, Mahfud Sholihin, M.Acc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Sugar cane industry in Indonesia is one of the most prospective businesses to be developed. Population growth, increasing in purchasing power and tremendous growth in food and beverage industry have driven the demand for sugar cane. In the end of year 2011, the domestic sugar cane industry was still lack of supply to meet the sugar demand. One of strategy to develop sugar cane industry is to build the hybrid sugar mill. The hybrid mill is a plant that processes both sugar cane and imported raw sugar interchangeably throughout the year. Raw material is obtained from the over supplied sugar cane in East Java that is not processed by incumbent sugar mills. A business feasibility study is needed to assess that business development plan. This research is a feasibility study that analyzes and covers several business aspects such as macro environment, industry environment and financial aspects as well. This study concluded that the hybrid sugar mill in East Java is a fit strategy and is a viable business to be executed.